2018
DOI: 10.1080/10495398.2018.1476376
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitogenome reveals genetic divergence and phylogenetic relationships among Indian cattle (Bos indicus) breeds

Abstract: Indigenous cattle of India belong to the species, Bos indicus and they possess various adaptability and production traits. However, little is known about the genetic diversity and origin of these breeds. To investigate the status, we sequenced and analyzed the whole mitochondrial DNA (mtDNA) of seven Indian cattle breeds. In total, 49 single-nucleotide variants (SNVs) were identified among the seven breeds analyzed. We observed a common synonymous SNV in the COII gene (m.7583G > A) of all the breeds studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…The number of registered cattle breeds in India has increased steadily over time, with Sukhatme [ 13 ] reporting 26 cattle breeds in 1968 and the National Bureau of Animal Genetic Resources ( http://www.nbagr.res.in/nbagr.html ) listing 50 registered Indian cattle breeds to date. Five of these registered breeds—Sahiwal, Gir, Red Sindhi, Tharparkar, and Deoni—are pure milking breeds, whereas the others are dual purpose or pure draught animals [ 14 , 15 ]. Only a small percentage of the Indian indigenous breeds are raised as pure breeds and the large majority of cattle used by smallholder farmers are of non-descript breeds [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of registered cattle breeds in India has increased steadily over time, with Sukhatme [ 13 ] reporting 26 cattle breeds in 1968 and the National Bureau of Animal Genetic Resources ( http://www.nbagr.res.in/nbagr.html ) listing 50 registered Indian cattle breeds to date. Five of these registered breeds—Sahiwal, Gir, Red Sindhi, Tharparkar, and Deoni—are pure milking breeds, whereas the others are dual purpose or pure draught animals [ 14 , 15 ]. Only a small percentage of the Indian indigenous breeds are raised as pure breeds and the large majority of cattle used by smallholder farmers are of non-descript breeds [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies on the genetic diversity of Bos indicus cattle are still lacking. Among the studies reported in the literature, some have used limited numbers of mitochondrial DNA markers [ 14 , 16 , 17 ], or a few selected autosomal microsatellite or single nucleotide polymorphisms (SNPs) [ 16 , 18 20 ], and others have analyzed a limited number of breeds from India [ 21 ], or indicine breeds from other countries [ 17 , 22 ]. Thus, relatively little is known about the genetic diversity of Indian cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates, based on genome-wide sequence data, place the evolutionary divergence time between the two cattle subspecies at 150 to 500 kya (Chen et al 2018;Wang et al 2018;Wu et al 2018), although some analyses of complete mitogenomes have suggested a deeper split (Hiendleder et al 2008;Bibi 2013;Pramod et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent sequencing and analysis of the complete mitochondrial genome of seven Indian cattle breeds indicates that in addition to the previously known domestication of a sub-species of Aurochs within the Indus Valley around 6500 BCE, another domestication location in Southern India also gave rise to the humped zebu cattle: B. indicus [42]. A earlier assumption that B. taurus arose from a point source domestication of Aurochs around 8500 BCE within the Fertile Crescent—the region of the Tigris and Euphrates Rivers within Iran and Iraq extending east across from the Persian Gulf towards and southwards along the eastern border of the Mediterranean Sea—has been disproven in recent studies [43,44,45,46,47,48].…”
Section: Cattle Domestication and Early Religious Symbolismmentioning
confidence: 99%